Evaluasi Pemanfaatan Potensi Pariwisata Melalui Pendekatan Community Based Tourism Di Desa Botutonuo Kecamatan Kabila Bone Kabupaten Bone Bolango - Suleman, Syahputra Adisanjaya; Arsyad, Yolandika (Jurnal Publisitas, 2024)
This research aims to describe the utilization of tourism potential and the implementation of the Community Based Tourism (CBT) approach in tourism management in Botutonuo Village, Kabila Bone District, Bone Bolango Regency. CBT is a tourism management approach that makes the community as the main actor, so that the results or benefits of tourism activities can be used to create welfare for the surrounding community. The manifestation of CBT is the development of tourist villages that utilize the potential of natural, cultural and human resources. By using qualitative research methods, this research shows that the CBT approach has been applied to educate the public regarding community-based tourism management, including by making processed products that have economic value, preserving the underwater environment, as well as preserving Gorontalo culture involving the surrounding community. However, in the management of tourism potential, there are still conflicts between local communities and investors and the village government which hinders the progress and sustainability of tourism in Botutonuo Village. Tourism development using the CBT model has actually been carried out by the community and village government, although the results have not been optimal and still require assistance so that the long-term goal of CBT,to create prosperity for local communities can be achieved.